AB0589 The role of anca specificity in the clinical manifestations at disease onset: comparison between patients with granulomatosis with polyangiitis and microscopic polyangiitis. (15th June 2017) - Monti, S; Felicetti, M; Balduzzi, S; Padoan, R; Berti, A; Paolazzi, G; Brunori, G; Schiavon, F; Caporali, R
Abstract : Background: ANCA specificity, rather than clinical diagnosis, has been suggested to influence the phenotype and clinical course of ANCA associated vasculitis (AAV) (1, 2). Objectives: To investigate differences in clinical presentation at disease onset between MPO-ANCA-positive granulomatosis with polyangiitis patients (MPO-GPA), PR3-ANCA-positive-GPA (PR3-GPA), and MPO-ANCA-positive microscopic polyangiitis (MPO-MPA). Methods: Clinical records of AAV patients from three third level rheumatologic centers in Northern Italy were retrospectively analyzed. Results: Of the 133 AAV patients included, 84 were PR3-GPA, 24 MPO-GPA, and 25 MPO-MPA. Patients with MPO-MPA were significantly older at diagnosis compared to both PR3-GPA and MPO-GPA (average age 63±10, 49±15, 55±29, respectively) (Table 1 ). Patients with MPO-GPA experienced a significant diagnostic delay compared to PR3-GPA (17±30 vs 7±14, p=0.02). ENT involvement was equally frequent in both GPA groups despite ANCA specificity, and significantly more represented than the MPO-MPA group (68%, 71% and 17% respectively; p<0.001). Figure 1 . Renal involvement was significantly more frequent in MPO-MPA patients (100%) compared to GPA (p<0.001), without differences between MPO-GPA (46%) and PR3-GPA (65%). Alveolar haemorrhage (DAH) was an onset manifestation mainly in MPO-MPA compared to the other two groups (24% vs 7% in PR3-GPA; p=0.02). Cutenous manifestations, mainly purpura, were significantly more reported in PR3-GPA compared to MPO-MPA (29% vs 4%; p=0.03). Conclusions: Clinical phenotype of GPA at disease onset did not seem to be influenced by ANCA specificity. Despite ANCA positivity (PR3 or MPO), GPA patients were significantly different from MPA. References: Schirmer JH, Wright MN, Herrmann K, et al. Myeloperoxidase-Antineutrophil Cytoplasmic Antibody (ANCA)-Positive Granulomatosis With Polyangiitis (Wegener's) Is a Clinically Distinct Subset of ANCA-Associated Vasculitis: A Retrospective Analysis of 315 Patients From a German Vasculitis Referral Center. Arthritis Rheumatol Hoboken NJ 2016;68:2953–63. Miloslavsky EM, Lu N, Unizony S, et al. Myeloperoxidase-Antineutrophil Cytoplasmic Antibody (ANCA)-Positive and ANCA-Negative Patients With Granulomatosis With Polyangiitis (Wegener's): Distinct Patient Subsets. Arthritis Rheumatol 2016;68:2945–2952. Disclosure of Interest: None declared